The Effect of Using Intensive and Extensive Techniques to Develop Iraqi Learners' Ability in Reading Comprehension (Journal of the College of Basic Education, 2026)
Reading comprehension is considered to be the most useful and important skill that occupies an important goal in the teaching English as a FL. It can be said that teaching FL is not teaching reading skill, but reading comprehension skill is an important in teaching language as all. This study aims at investigating the effect of using intensive and extensive techniques in teaching reading comprehension on the achievement of the second stage. The following null hypothesis has been posed: "There is no a statistically significant difference between the achievement scores of the subjects in the pre-and the post test of reading comprehension." It is found that the success of intensive and extensive techniques led to an important change in students' performance in learning FL. In the light of the outcomes, some recommendations and suggestions for further studies are made.